Perilaku Struktur Bangunan Joglo Lambang Gantung Pendapa Agung Dalem Mangkubumen Yogyakarta akibat Gaya Lateral - YE. Suharno; Tri Yuniastuti; Bayu Dwi Wismantoro (JURNAL ARSITEKTUR PENDAPA, 2023)
The beauty of Pendapa Agung Mangkubumen which is located in the Dalem Mangkubumen area has not been widely revealed. Pendapa Agung Dalem Mangkubumen has the uniqueness of using a pole structure located at the corner of the takir cross and hanging from the dudur to function as a place to attach the sunduk lambang gantung and behave as a pull rod. While the sunduk serves as a place for the long wood and the roof of the penanggap. This fringe roof is completely dependent on the rods so that it can freely sway when exposed to lateral forces. The purpose of this study is to examine in detail the resistance of the lambang gantung structure used in Pendapa Agung Dalem Mangkubumen against lateral forces. The research method used is observation and modeling the structure of Pendapa Agung Dalem Mangkubumen into a miniature form. The next step is structural stability analysis by testing the model against lateral forces using an earthquake resistant simulation tool (SIMUTAGA). The result of this research is that Pendapa Agung Dalem Mangkubumen is still able to withstand lateral movement with moderate vibration on a scale IV – V MMI. As a result of this movement, several Saka Guru columns shifted from their original position of about 5 mm and the sunduk kili connection was slightly stretched from its original position of about 2 mm. Meanwhile, in the South-West corner, three penanggap columns collapsed and their purus was released.